2014
DOI: 10.1159/000361023
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antibodies in Oral Immunotherapy for Cow's Milk Allergy: Kinetics and Prediction of Clinical Outcome

Abstract: Background: Methods for predicting the clinical outcome of specific oral immunotherapy (OIT) would improve the safety of the therapy. Methods: We investigated 40 children aged 6-17 years with IgE-mediated cow's milk allergy (CMA) who either successfully completed OIT (n = 32) or discontinued the therapy due to adverse reactions (n = 8). From sera drawn before and after OIT, we analyzed specific IgA, IgG, IgG1 and IgG4 to cow's milk (CM), casein, β-lactoglobulin and ovalbumin (with enzyme-linked immunosorbent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
4
23
1
6
Order By: Relevance
“…Food-specific IgG4 decreases the following dietary elimination of the offending food [71] . Allergen-specific IgG and IgA increase after OIT [72] . Allergen-specific IgG subclasses (1-4) and IgA are able to bind to an allergen, act as an immune complex, and activate eosinophils; hence, they can induce eosinophil activation after SLIT or OIT and probably lead to the development of EoE [73] .…”
Section: Oit and Eosinophilic Esophagitismentioning
confidence: 93%
“…Food-specific IgG4 decreases the following dietary elimination of the offending food [71] . Allergen-specific IgG and IgA increase after OIT [72] . Allergen-specific IgG subclasses (1-4) and IgA are able to bind to an allergen, act as an immune complex, and activate eosinophils; hence, they can induce eosinophil activation after SLIT or OIT and probably lead to the development of EoE [73] .…”
Section: Oit and Eosinophilic Esophagitismentioning
confidence: 93%
“…Baseline egg-specific IgE was reported to be a useful parameter to help identify children in whom egg OIT is more likely to be safe [46]. In the case of cow's milk allergy, high specific IgE, IgA, and IgG isotype antibodies to cow's milk were indicators of treatment failure in a study [47] of 40 children undergoing cow's milk OIT. These findings suggest novel strategies that may help with patient selection and risk stratification, which might maximize overall safety and effectiveness of immunotherapy.…”
Section: Lessons From Recent Advancements In Oral Immunotherapy For Tmentioning
confidence: 99%
“…Serum levels of peanut-specific IgE, IgG, and IgG4 antibodies were measured at each visit, since these are known biomarkers of allergic responses, antigen exposure, and potential immune modulation, respectively. 26,27 The peanut-specific IgG4:IgE ratio was calculated, since it has been reported that this ratio may additionally reflect immune modulation. 28 Immunoglobulin measurements were made with the use of the ImmunoCAP 100 and 250 assays (Thermo Fisher Scientific).…”
Section: Immune Markersmentioning
confidence: 99%